The age of analysis : 20th century philosophers - White, Morton Gabriel, 1917- ([New York] : New American Library, 1955)
Basic writings of Henri Bergson, Charles Sanders Peirce, Alfred North Whitehead, William James, Benedetto Croce, Bertrand Russell, Ludwig Wittgenstein, George Santayana, John Dewey, Jean Paul Sartre, and others.
The decline and fall of the absolute --
The revival of realism and common sense: G.E. Moore --
Philosophy and history: Benedetto Croce --
Myth, morals, and religion: George Santayana --
Time, instinct, and freedom: Henri Bergson --
Nature and life: Alfred North Whitehead --
Phenomenology: Edmund Husserl --
Existentialism: Jean-Paul Sartre --
Pragmatism and meaning: Charles Sanders Peirce --
Truth and practice: William James --
Science and morals: John Dewey --
Mathematics, logic, and analysis: Bertrand Russell --
Logical positivism: Rudolf Carnap --
The uses of language: Ludwig Wittgenstein --
Philosophy and man: an exhortation.
Keywords: Philosophy, Modern -- 20th century